Lord Brocktree - Jacques, Brian; Fangorn (New York : Philomel Books, 2000)
The mountain of Salamandastron needs the help of Brocktree the Badger Lord when evil comes in the form of the Blue Hordes of Ungatt Trunn, the Earth Shaker.
Wilson's Junior High School.
School Library Journal.
Booklist.
6.3
5-8
Keywords: Badgers -- Fiction; Animals -- Fiction; Fantasy; Badgers -- Fiction; Animals -- Fiction; Fantasy fiction; Badgers -- Fiction; Animals -- Fiction; Fantasy